Primary production in relation to algal species composition in a warming Western Antarctic peninsula - Maria A. van Leeuwe; Alison L. Webb; Mareike G. Bach; Michael P. Meredith; Desiree den Os; Jacqueline Stefels (Journal of Marine Systems, 2026)

The emerging and escalating consequences of rural depopulation in the Himalaya - Karuna Budhathoki; Bhola Bhattarai; Bed Mani Dahal; Shalini Dhyani; Ambika P. Gautam; Binita Guragain; Dibya Devi Gurung; Muhammad Ismail; Om Katel; Sarala Khaling; Kristina Marquardt; Ulrike Müller-Böker; et al. (Global Environmental Change, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interdisciplinary, community-engaged training on endocrine-disrupting chemicals: bridging science, communication, justice and policy for environmental health - Rose M. Albert; Jenna K. Honan; Gabrielle P. Webb; Luyu Wang; Joseph Tucker; Sarvenaz Shahin; Eleanor Medley; Jean-Marie Kauth; Roberto Sempere-Navarro; Ariel Christensen; Debojyoti Chakraborty; Lissah Johnson; et al. (Journal of Environmental Studies and Sciences, 2026)

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Early Paleozoic magmatism in the Himalaya linked with a peri-Gondwana silicic large igneous province - Dominik R. Vlaha; Andrew V. Zuza; Ariuntsetseg Ganbat; Chen Wu; Peter J. Haproff; Victor E. Guevara; A. Alexander G. Webb; Marie C. Genge; Birendra P. Singh (Tectonophysics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

An updated Irwin sensor for measurement of surface shear velocity - Nancy P. Ziegler; Nicholas P. Webb; Brandon L. Edwards; George Nikolich; John A. Gillies; Sahil G. Patel; Brandi Wheeler; Pei Zhang; Justin W. Van Zee; Sandra L. LeGrand; Andrew C. Trautz (Aeolian Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Evolving physical and mechanical rock properties during exposure at Earth's surface - Monica Rasmussen; Martha Cary Eppes; Yang Yuan; Philip G. Meredith; Karin Hofer Apostolidis; Thomas Mitchell; Alex J. Rinehart; Amit Mushkin; Patrick Webb; Valerie Reynolds; Alan J. Hidy; Samantha Berberich; et al. (Geomorphology, 2025)

Decision-making Dynamics of Pregnant and Lactating Women (PLW) Participating in a Community Health and Nutrition Intervention in Jordan - R. Brown; L. Miller; Y. Ren; I. Moore; A. Alghanmi; r. Safadi; P. Webb; R. Shrestha; S. Ghosh (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluation of the WEPS hydrology sub-model for surface soil water content under different tillage practices in the inland Pacific Northwest, USA - Huawei Pi; David R. Huggins; Larry.E. Wagner; Fred. Fox; Sisi Li; Nicholas P. Webb (CATENA, 2025)

Crushing energy-based indicators of dry soil aggregate stability from contrastive land management practices in a semi-arid agroecosystem - Huawei Pi; Chuanzhou Wang; Sifeng Li; Sisi Li; Nicholas P. Webb (Ecological Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Bioanalytical Method Comparison Strategy for Clinical Anti-drug Antibody Immunoassays - R. J. Elliott; T. Pourmohamad; Y. Webb-Vargas; W. Yan; I. Nijem; P. Siguenza; Y. Song (The AAPS Journal, 2024)
Per FDA guidance, method comparability should be established if an anti-drug antibody (ADA) assay is run by two or more independent laboratories during a study. Genentech, Inc. is evaluating an immunogenicity risk-based comparability approach consisting of both technical and clinical aspects. Technical comparability of the relative sensitivity (RS) is assessed using the Two One-Sided T-tests (TOST) statistical analysis which evaluates if the difference (in absolute value) of the RS means of the two laboratories is less than a pre-specified level of comparability, the practically significant difference (PSD). Clinical comparability is based on the molecule’s immunogenicity risk. A basic and in-depth assessment for low and high-risk molecules are used, respectively. An alternative strategy for molecules with limited incurred sample availability is to be used. In the basic assessment, samples are either unfortified or fortified with surrogate ADA positive control at method appropriate concentrations in a representative biological matrix. Acceptable comparability requires in both methods i) at least 80% of the unfortified samples screen and confirm negative, ii) at least 90% of the low concentration samples screen and confirm positive; and iii) 100% of the high concentration samples screen and confirm positive. The in-depth assessment uses at least 100 incurred samples from 30 or more ADA-positive and ADA-negative patients. The results are evaluated using a 2 by 2-confusion matrix and Cohen’s Kappa score where 1 indicates perfect agreement. Acceptable comparability requires a Cohen’s Kappa score of greater than 0.40. This strategy allows for a robust technical and clinical method comparability assessment. Graphical Abstract

An evaluation of different approaches for estimating shear velocity in aeolian research studies - Pei Zhang; Brandon L. Edwards; Nicholas P. Webb; Andrew Trautz; John A. Gillies; Nancy P. Ziegler; Justin W. Van Zee (Aeolian Research, 2024)

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Influence of crop rotation, irrigation, fertilization, and tillage on the aggregate property and soil wind erosion potential in the floodplain of the Yellow River - Huawei Pi; Xiuli Zhang; Sisi Li; Nicholas P. Webb (Aeolian Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia - Michele Potashman; Katja Rudell; Ivanna Pavisic; Naomi Suminski; Rinchen Doma; Maggie Heinrich; Linda Abetz-Webb; Melissa Wolfe Beiner; Sheng-Han Kuo; Liana S. Rosenthal; Theresa Zesiwicz; Terry D. Fife; et al. (The Cerebellum, 2024)
The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 ( n = 1) and SCA3 ( n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of SCA and relevance of f-SARA concepts for SCA. HCP cognitive debriefing was conducted. Interviews were recorded, transcribed, coded, and analyzed by ATLAS.TI software. Individuals with SCA1 and 3 reported 85 symptoms, signs, and impacts of SCA. All indicated difficulties with walking, stance, balance, speech, fatigue, emotions, and work. All individuals with SCA1 and 3 considered Gait, Stance, and Speech relevant f-SARA concepts; 3 considered Sitting relevant (42.9%). All HCPs considered Gait and Speech relevant; 5 (62.5%) indicated Stance was relevant. Sitting was considered a late-stage disease indicator. Most HCPs suggested inclusion of appendicular items would enhance clinical relevance. Cognitive debriefing supported clarity and comprehension of f-SARA. Maintaining current abilities on f-SARA items for 1 year was considered meaningful for most individuals with SCA1 and 3. All HCPs considered meaningful changes as stability in f-SARA score over 1–2 years, 1–2-point change in total f-SARA score, and deviation from natural history. These results support content validity of f-SARA for assessing SCA disease progression in clinical trials.

Neoarchean lavas of the Ventersdorp Large Igneous Province, South Africa: Sr-Nd-Hf isotopic and trace element evidence for a long-lived plume beneath a stationary African continent - Khulekani B. Khumalo; Lewis D. Ashwal; Ben Hayes; Linda M. Iaccheri; P. Gerhard Meintjes; Susan J. Webb (Earth-Science Reviews, 2024)

Human-cattle interactions in PPNB and Early/Middle Bronze Age Cyprus: integrating zooarchaeological and stable isotope data - A. Spyrou; P. Roberts; M. Bleasdale; M. Lucas; L. Crewe; A Simmons; J. Webb (Archaeological and Anthropological Sciences, 2024)

A new framework for evaluating dust emission model development using dichotomous satellite observations of dust emission - Mark Hennen; Adrian Chappell; Nicholas P. Webb; Kerstin Schepanski; Matthew C. Baddock; Frank D. Eckardt; Tarek Kandakji; Jeffrey A. Lee; Mohamad Nobakht; Johanna von Holdt (Science of The Total Environment, 2024)

Comparative stable isotope analyses of green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) in the San Francisco estuary - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Molly Webb; A. Peter Klimley (Journal of Fish Biology, 2024)
Green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) are closely related, sympatric species that inhabit the San Francisco estuary. Green sturgeon have a more marine life history but both species spawn in the Sacramento River and reside for some duration in San Francisco Bay. These sturgeons are of conservation concern, yet little is known about their dietary competition when they overlap in space and time. To examine evidence of dietary differentiation, we collected whole blood and blood plasma from 26 green sturgeon and 35 white sturgeon in San Francisco Bay. Using carbon and nitrogen stable isotope analyses, we compared their relative trophic levels and foraging locations along the freshwater to marine gradient. Sampling blood plasma and whole blood allowed comparison of dietary integration over shorter and longer time scales, respectively. Plasma and whole blood δ 13 C values confirmed green sturgeon had more marine dietary sources than white sturgeon. Plasma δ 15 N values revealed white sturgeon fed at lower trophic levels than green sturgeon recently, however, whole blood δ 15 N values demonstrated the two species fed at the same trophic level over longer time scales. Larger individuals of both species had higher δ 13 C values than smaller individuals, reflecting more marine food sources in adulthood. Length did not affect δ 15 N values of either species. Isotope analyses supported the more marine life history of green than white sturgeon and potentially highlight a temporary trophic differentiation of diet between species during and preceding the overlapping life stage in San Francisco Bay.

Comparative analysis of animal lifespan - Nicole C. Riddle; Peggy R. Biga; Anne M. Bronikowski; James R. Walters; Gerald S. Wilkinson; Jingyue Ellie Duan; Anthony Gamble; Erica Larschan; Richard P. Meisel; Ritambhara Singh; Ashley Webb (GeroScience, 2023)
Comparative studies of aging are a promising approach to identifying general properties of and processes leading to aging. While to date, many comparative studies of aging in animals have focused on relatively narrow species groups, methodological innovations now allow for studies that include evolutionary distant species. However, comparative studies of aging across a wide range of species that have distinct life histories introduce additional challenges in experimental design. Here, we discuss these challenges, highlight the most pressing problems that need to be solved, and provide suggestions based on current approaches to successfully carry out comparative aging studies across the animal kingdom.

Synergistic soil, land use, and climate influences on wind erosion on the Colorado Plateau: Implications for management - Travis W. Nauman; Seth M. Munson; Saroj Dhital; Nicholas P. Webb; Michael C. Duniway (Science of The Total Environment, 2023)

S12-01: Physiologically-Based Kinetic (PBK) Models and Applications In Read-Across - J. Madden; C. Thompson; S. Webb; P. Penson; C. Tan; A. Paini (Toxicology Letters, 2023)

Managing an arid ranch in the 21st century: New technologies for novel ecosystems - Brandon T. Bestelmeyer; Santiago Utsumi; Sarah McCord; Dawn M. Browning; Laura M. Burkett; Emile Elias; Rick Estell; Jeffrey Herrick; Darren James; Sheri Spiegal; Nicholas P. Webb; Jebediah Williamson (Rangelands, 2023)

Satellites reveal Earth's seasonally shifting dust emission sources - Adrian Chappell; Nicholas P. Webb; Mark Hennen; Kerstin Schepanski; Philippe Ciais; Yves Balkanski; Charles S. Zender; Ina Tegen; Zhenzhong Zeng; Daniel Tong; Barry Baker; Marie Ekström; et al. (Science of The Total Environment, 2023)

Harnessing biodiversity data to inform policy: Rapid regional audits should underpin Local Nature Recovery Strategies - Liam P. Crowther; James J. Gilroy; Robert W. Hawkes; Will J. Peach; Daniel Salliss; Jonathan R. Webb; Paul M. Dolman (Biological Conservation, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

The role of standards in biofilm research and industry innovation - S.A. Wade; J.S. Webb; R.B. Eckert; G.E. Jenneman; S.A. Rice; T.L. Skovhus; P. Sturman; S.P. Kotu; M. Richardson; D.M. Goeres (International Biodeterioration & Biodegradation, 2023)

A preliminary investigation of the effect of solar panels and rotation frequency on the grazing behavior of sheep (Ovis aries) grazing dormant pasture - Emma W. Kampherbeek; Laura E. Webb; Beth J. Reynolds; Seeta A. Sistla; Marc R. Horney; Raimon Ripoll-Bosch; Jason P. Dubowsky; Zachary D. McFarlane (Applied Animal Behaviour Science, 2023)

Modelled direct causes of dust emission change (2001–2020) in southwestern USA and implications for management - Mark Hennen; Adrian Chappell; Nicholas P. Webb (Aeolian Research, 2023)

Forecasting solar photosynthetic photon flux density under cloud cover effects: novel predictive model using convolutional neural network integrated with long short-term memory network - Ravinesh C. Deo; Richard H. Grant; Ann Webb; Sujan Ghimire; Damien P. Igoe; Nathan J. Downs; Mohanad S. Al-Musaylh; Alfio V. Parisi; Jeffrey Soar (Stochastic Environmental Research and Risk Assessment, 2022)
Forecast models of solar radiation incorporating cloud effects are useful tools to evaluate the impact of stochastic behaviour of cloud movement, real-time integration of photovoltaic energy in power grids, skin cancer and eye disease risk minimisation through solar ultraviolet (UV) index prediction and bio-photosynthetic processes through the modelling of solar photosynthetic photon flux density (PPFD). This research has developed deep learning hybrid model (i.e., CNN-LSTM) to factor in role of cloud effects integrating the merits of convolutional neural networks with long short-term memory networks to forecast near real-time (i.e., 5-min) PPFD in a sub-tropical region Queensland, Australia. The prescribed CLSTM model is trained with real-time sky images that depict stochastic cloud movements captured through a total sky imager (TSI-440) utilising advanced sky image segmentation to reveal cloud chromatic features into their statistical values, and to purposely factor in the cloud variation to optimise the CLSTM model. The model, with its competing algorithms (i.e., CNN, LSTM, deep neural network, extreme learning machine and multivariate adaptive regression spline), are trained with 17 distinct cloud cover inputs considering the chromaticity of red, blue, thin, and opaque cloud statistics, supplemented by solar zenith angle (SZA) to predict short-term PPFD . The models developed with cloud inputs yield accurate results, outperforming the SZA -based models while the best testing performance is recorded by the objective method (i.e., CLSTM) tested over a 7-day measurement period. Specifically, CLSTM yields a testing performance with correlation coefficient r = 0.92, root mean square error RMSE = 210.31 μ mol of photons m −2 s −1 , mean absolute error MAE = 150.24 μ mol of photons m −2 s −1 , including a relative error of RRMSE = 24.92% MAP E = 38.01%, and Nash Sutcliffe’s coefficient E NS = 0.85, and Legate and McCabe’s Index LM = 0.68 using cloud cover in addition to the SZA as an input. The study shows the importance of cloud inclusion in forecasting solar radiation and evaluating the risk with practical implications in monitoring solar energy, greenhouses and high-value agricultural operations affected by stochastic behaviour of clouds. Additional methodological refinements such as retraining the CLSTM model for hourly and seasonal time scales may aid in the promotion of agricultural crop farming and environmental risk evaluation applications such as predicting the solar UV index and direct normal solar irradiance for renewable energy monitoring systems.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Combined reduced expression of two gene families lowers nicotine content to ultra-low levels in cultivated tobacco - Sheri P. Kernodle; Sydney Webb; Tyler M. Steede; Ramsey S. Lewis (Plant Cell Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Unveiling hidden sponge biodiversity within the Hawaiian reef cryptofauna - Jan Vicente; Maryann K. Webb; Gustav Paulay; Wachirawit Rakchai; Molly A. Timmers; Christopher P. Jury; Keisha Bahr; Robert J. Toonen (Coral Reefs, 2022)

Organochlorine and Metal Contaminants in the Blood Plasma of Green Sturgeon Caught in Washington Coastal Estuaries - Julie A. Layshock; Molly A. H. Webb; Olaf P. Langness; John Carlos Garza; Laura B. Heironimus; Deke Gundersen (Archives of Environmental Contamination and Toxicology, 2022)

Early inflammation precedes cardiac fibrosis and heart failure in desmoglein 2 murine model of arrhythmogenic cardiomyopathy - K. E. Ng; P. J. Delaney; D. Thenet; S. Murtough; C. M. Webb; N. Zaman; E. Tsisanova; G. Mastroianni; S. L. M. Walker; J. D. Westaby; D. J. Pennington; R. Pink; et al. (Cell and Tissue Research, 2021)
The study of a desmoglein 2 murine model of arrhythmogenic cardiomyopathy revealed cardiac inflammation as a key early event leading to fibrosis. Arrhythmogenic cardiomyopathy (AC) is an inherited heart muscle disorder leading to ventricular arrhythmias and heart failure due to abnormalities in the cardiac desmosome. We examined how loss of desmoglein 2 ( Dsg2 ) in the young murine heart leads to development of AC. Apoptosis was an early cellular phenotype, and RNA sequencing analysis revealed early activation of inflammatory-associated pathways in Dsg2 -null ( Dsg2 −/− ) hearts at postnatal day 14 (2 weeks) that were absent in the fibrotic heart of adult mice (10 weeks). This included upregulation of iRhom2/ADAM17 and its associated pro-inflammatory cytokines and receptors such as TNFα, IL6R and IL-6. Furthermore, genes linked to specific macrophage populations were also upregulated. This suggests cardiomyocyte stress triggers an early immune response to clear apoptotic cells allowing tissue remodelling later on in the fibrotic heart. Our analysis at the early disease stage suggests cardiac inflammation is an important response and may be one of the mechanisms responsible for AC disease progression.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Annual patterns in phytoplankton phenology in Antarctic coastal waters explained by environmental drivers - Maria A. van Leeuwe; Alison L. Webb; Hugh J. Venables; Ronald J.W. Visser; Mike P. Meredith; J. Theo M. Elzenga; Jacqueline Stefels (Limnology and Oceanography, 2020)
Coastal zones of Antarctica harbor rich but highly variable phytoplankton communities. The mechanisms that control the dynamics of these communities are not well defined. Here we elucidate the mechanisms that drive seasonal species succession, based on algal photophysiological characteristics and environmental factors. For this, phytoplankton community structure together with oceanographic parameters was studied over a 5‐year period (2012–2017) at Rothera Station at Ryder Bay (Western Antarctic Peninsula). Algal pigment patterns and photophysiological studies based on fluorescence analyses were combined with data from the Rothera Time‐Series program. Considerable interannual variation was observed, related to variations in wind‐mixing, ice cover and an El Niño event. Clear patterns in the succession of algal classes became manifest when combining the data collected over the five successive years. In spring, autotrophic flagellates with a high light affinity were the first to profit from increasing light and sea ice melt. These algae most likely originated from sea‐ice communities, stressing the role of sea ice as a seeding vector for the spring bloom. Diatoms became dominant towards summer in more stratified and warmer surface waters. These communities displayed significantly lower photoflexibility than spring communities. There are strong indications for mixotrophy in cryptophytes, which would explain much of their apparently random occurrence. Climate models predict continuing retreat of Antarctic sea‐ice during the course of this century. For the near‐future we predict that the marginal sea‐ice zone will still harbor significant communities of haptophytes and chlorophytes, whereas increasing temperatures will mainly be beneficial for diatoms.

Genetic structures across a biogeographical barrier reflect dispersal potential of four Southeast Asian mangrove plant species - Alison K. S. Wee; Annika M. E. Noreen; Junya Ono; Koji Takayama; Prakash P. Kumar; Hugh T. W. Tan; Mohd N. Saleh; Tadashi Kajita; Edward L. Webb (Journal of Biogeography, 2020)
Aim Biogeographical barriers restrict the movement of individuals, resulting in population divergence, genetic differentiation, endemism and speciation. Yet, some barriers demonstrate unequal effect across species depending on species dispersal, which manifests in varying genetic structure. We test the hypotheses that the genetic structure of four coastal mangrove species would reflect differences in dispersal potential across the Malay Peninsula, a major biogeographical barrier in the Indo‐West Pacific region. Location East and west coasts of the Malay Peninsula. Taxon Mangrove trees Avicennia alba , Sonneratia alba , Bruguiera gymnorhiza and Rhizophora mucronata. Methods For each species, we characterized genetic structure and gene flow using 7–12 species‐specific nuclear microsatellite markers. We tested for east–west genetic differentiation across the peninsula, a stepping‐stone migration pattern, and assessed the proportion of recent dispersal and direction of historical migration along the Malacca Strait. Results Significant east–west genetic differentiation across the peninsula was observed in A. alba , S. alba and B. gymnorhiza , and the effect was most pronounced for the two species with lower dispersal potential ( A. alba , S. alba ). In contrast, the two species with higher dispersal potential ( B. gymnorhiza and R. mucronata ) exhibited much higher proportion of recent inter‐population migration along the Malacca Strait. The signature of historical colonization from refugia in the Andaman Sea (north‐to‐south migration along the Malacca Strait) predominated for A. alba and S. alba. Historical south–north migration predominated for R. mucronata and B. gymnorhiza . Main conclusions This study implicated dispersal potential as a cause of varying mangrove species genetic structure across a biogeographical barrier. The Malay Peninsula functions as a filter to gene flow rather than a barrier. The genetic structure in mangrove species with a higher dispersal potential is more congruent with contemporary gene flow while that of species with a lower dispersal potential reflects historical processes. Our findings hint at the role of dispersal potential as a predictor of gene flow in mangroves.

Dietary inflammatory index, risk and survival among women with endometrial cancer - C. M. Nagle; T. Ibiebele; N. Shivappa; J. R. Hébert; A. B. Spurdle; P. M. Webb (Cancer Causes & Control, 2020)

How accurately can the climate sensitivity to $$\hbox {CO}_{2}$$ be estimated from historical climate change? - J. M. Gregory; T. Andrews; P. Ceppi; T. Mauritsen; M. J. Webb (Climate Dynamics, 2020)
The equilibrium climate sensitivity (ECS, in K) to $$\hbox {CO}_{2}$$ CO 2 doubling is a large source of uncertainty in projections of future anthropogenic climate change. Estimates of ECS made from non-equilibrium states or in response to radiative forcings other than $$\hbox {2}× \hbox {CO}_{2}$$ 2 × CO 2 are called “effective climate sensitivity” (EffCS, in K). Taking a “perfect-model” approach, using coupled atmosphere–ocean general circulation model (AOGCM) experiments, we evaluate the accuracy with which $$\hbox {CO}_{2}$$ CO 2 EffCS can be estimated from climate change in the “historical” period (since about 1860). We find that (1) for statistical reasons, unforced variability makes the estimate of historical EffCS both uncertain and biased; it is overestimated by about 10% if the energy balance is applied to the entire historical period, 20% for 30-year periods, and larger factors for interannual variability, (2) systematic uncertainty in historical radiative forcing translates into an uncertainty of $${± }\,30\, {\rm to} \,45%$$ ± 30 to 45 % (standard deviation) in historical EffCS, (3) the response to the changing relative importance of the forcing agents, principally $$\hbox {CO}_{2}$$ CO 2 and volcanic aerosol, causes historical EffCS to vary over multidecadal timescales by a factor of two. In recent decades it reached its maximum in the AOGCM historical experiment (similar to the multimodel-mean $$\hbox {CO}_{2}$$ CO 2 EffCS of 3.6 K from idealised experiments), but its minimum in the real world (1.6 K for an observational estimate for 1985–2011, similar to the multimodel-mean value for volcanic forcing). The real-world variations mean that historical EffCS underestimates $$\hbox {CO}_{2}$$ CO 2 EffCS by 30% when considering the entire historical period. The difference for recent decades implies that either unforced variability or the response to volcanic forcing causes a much stronger regional pattern of sea surface temperature change in the real world than in AOGCMs. We speculate that this could be explained by a deficiency in simulated coupled atmosphere–ocean feedbacks which reinforce the pattern (resembling the Interdecadal Pacific Oscillation in some respects) that causes the low EffCS. We conclude that energy-balance estimates of $$\hbox {CO}_{2}$$ CO 2 EffCS are most accurate from periods unaffected by volcanic forcing. Atmosphere GCMs provided with observed sea surface temperature for the 1920s to the 1950s, which was such a period, give a range of about 2.0–4.5 K, agreeing with idealised $$\hbox {CO}_{2}$$ CO 2 AOGCM experiments; the consistency is a reason for confidence in this range as an estimate of $$\hbox {CO}_{2}$$ CO 2 EffCS. Unless another explosive volcanic eruption occurs, the first 30 years of the present century may give a more accurate energy-balance historical estimate of this quantity.

Co-development of a climate change decision support framework through engagement with stakeholders - Anne M. Leitch; J. P. Palutikof; D. Rissik; S. L. Boulter; Fahim N. Tonmoy; S. Webb; A. C. Perez Vidaurre; M. C. Campbell (Climatic Change, 2019)

CoastAdapt: an adaptation decision support framework for Australia’s coastal managers - J. P. Palutikof; D. Rissik; S. Webb; Fahim N. Tonmoy; S. L. Boulter; Anne M. Leitch; A. C. Perez Vidaurre; M. J. Campbell (Climatic Change, 2019)

Overcoming knowledge barriers to adaptation using a decision support framework - J. P. Palutikof; Anne M. Leitch; D. Rissik; S. L. Boulter; M. J. Campbell; A. C. Perez Vidaurre; S. Webb; Fahim N. Tonmoy (Climatic Change, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Meta-Analysis of the Effects of Computerized Cognitive Training on Executive Functions: a Cross-Disciplinary Taxonomy for Classifying Outcome Cognitive Factors - Shannon L. Webb; Vanessa Loh; Amit Lampit; Joel E. Bateman; Damian P. Birney (Neuropsychology Review, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Compound-specific amino acid isotopic proxies for distinguishing between terrestrial and aquatic resource consumption - Emily C. Webb; Noah V. Honch; Philip J. H. Dunn; Anna Linderholm; Gunilla Eriksson; Kerstin Lidén; Richard P. Evershed (Archaeological and Anthropological Sciences, 2018)

Increased energy differentially increases richness and abundance of optimal body sizes in deep‐sea wood falls - Craig R. McClain; James P. Barry; Thomas J. Webb (Ecology, 2018)
Theoretical and empirical studies suggest that the total energy available in natural communities influences body size as well as patterns of abundance and diversity. But the precise mechanisms underlying these relationships or how these three ecological properties relate remain elusive. We identify five hypotheses relating energy availability, body size distributions, abundance, and species richness within communities, and we use experimental deep‐sea wood fall communities to test their predicted effects both on descriptors describing the species‐richness–body‐size distribution, and on trends in species richness within size classes over an energy gradient (size‐class–richness relationships). Invertebrate communities were taxonomically identified, weighed, and counted from 32 Acacia sp. logs ranging in size from 0.6 to 20.6 kg (corresponding to different levels of energy available), which were deployed at 3,203 m in the Northeast Pacific Ocean for 5 and 7 yr. Trends in both the species‐richness–body‐size distribution and the size‐class–richness distribution with increasing wood fall size provide support for the Increased Packing hypothesis: species richness increases with increasing wood fall size but only in the modal size class. Furthermore, species richness of body size classes reflected the abundance of individuals in that size class. Thus, increases in richness in the modal size class with increasing energy were concordant with increases in abundance within that size class. The results suggest that increases in species richness occurring as energy availability increases may be isolated to specific niches, e.g., the body size classes, especially in communities developing on discrete and energetically isolated resources such as deep sea wood falls.

Effects of new-generation TMEM16A inhibitors on calcium-activated chloride currents in rabbit urethral interstitial cells of Cajal - Stephen Fedigan; Eamonn Bradley; Timothy Webb; Roddy J. Large; Mark A. Hollywood; Keith D. Thornbury; Noel G. McHale; Gerard P. Sergeant (Pflügers Archiv - European Journal of Physiology, 2017)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Immunotherapeutic strategies targeting natural killer T cell responses in cancer - Susannah C. Shissler; Dominique R. Bollino; Irina V. Tiper; Joshua P. Bates; Roshanak Derakhshandeh; Tonya J. Webb (Immunogenetics, 2016)

Thalassospira australica sp. nov. isolated from sea water - Elena P. Ivanova; Mario López-Pérez; Hayden K. Webb; Hooi Jun Ng; Thi Hoang Yen Dang; Natalia V. Zhukova; Valery V. Mikhailov; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Consensus Paper: Radiological Biomarkers of Cerebellar Diseases - Leonardo Baldarçara; Stuart Currie; M. Hadjivassiliou; Nigel Hoggard; Allison Jack; Andrea P. Jackowski; Mario Mascalchi; Cecilia Parazzini; Kathrin Reetz; Andrea Righini; Jörg B. Schulz; Alessandra Vella; et al. (The Cerebellum, 2015)

Bacterial patterning at the three-phase line of contact with microtextured alkanes - Song Ha Nguyen; Hayden K. Webb; David E. Mainwaring; Peter J. Mahon; Russell J. Crawford; Elena P. Ivanova (Biofouling, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Extrusion vs. duplexing models of Himalayan mountain building 3: duplexing dominates from the Oligocene to Present - Dian He; A. Alexander G. Webb; Kyle P. Larson; Aaron J. Martin; Axel K. Schmitt (International Geology Review, 2015)

Ecophysiological diversity of a novel member of the genus Alteromonas, and description of Alteromonas mediterranea sp. nov. - Elena P. Ivanova; Mario López-Pérez; Mila Zabalos; Song Ha Nguyen; Hayden K. Webb; Jason Ryan; Kiril Lagutin; Mikhail Vyssotski; Russell J. Crawford; Francisco Rodriguez-Valera (Antonie van Leeuwenhoek, 2015)

Projected changes in hailstorms during the 21st century over the UK - M. G. Sanderson; W. H. Hand; P. Groenemeijer; P. M. Boorman; J. D. C. Webb; L. J. McColl (International Journal of Climatology, 2015)
Hailstorms can pose a significant threat to society, by damaging property and disrupting livelihoods. An understanding of how hailstorm characteristics may change under a warming climate is therefore important for assessing the risk of hail damage for the insurance industry. A simple model of hailstone formation has been driven using meteorological data produced by a regional climate model (RCM) to project how hailstorm numbers and hailstone sizes could change during the 21st century in the UK . Evaluation of the modelled hailstone sizes, numbers and spatial distributions showed that they agreed reasonably well with observations. The effect of climate change on the numbers of damaging hailstorms in the UK (hailstones with diameters greater than 15 mm) was then investigated. A downward trend in the total number of damaging hailstorms during the 21st century was projected, with statistically significant trends for hailstones with diameters between 21 and 50 mm. Melting of hailstones made little contribution to the projected reductions. The results are subject to large uncertainties, some of which originate with the convective parameterization scheme used by the climate model.

Quaternary climatic instability in south‐east Australia from a multi‐proxy speleothem record - M. WEBB; J. DREDGE; P. A. BARKER; W. MÜLLER; C. JEX; J. DESMARCHELIER; J. HELLSTROM; P. M. WYNN (Journal of Quaternary Science, 2014)
Milankovitch‐scale Quaternary climatic oscillations within south‐east Australia are known to be characterized by relatively arid glacial and wet interglacial stages. However, terrestrial proxy records of environmental change are scarce, based largely on river terraces, dune sediments and pollen sequences. Here we present a speleothem‐based palaeoclimate record from Yarrangobilly caves, south‐east Australia. The oxygen isotopic composition of calcite (δ 18 O calcite ) is taken to represent rainfall amount and used as an aridity index. High‐resolution trace element profiles and UV fluorescence support interpretations based on δ 18 O calcite , allowing further designation of key phases of speleothem growth into periods of relative aridity and moisture excess. A hiatus of approximately 37 ka duration divides the record into two key phases of growth which can be mapped onto marine isotope stages 5c–a and 3, respectively. Increasing aridity in the latter half of MIS 5 led to cessation of speleothem growth for the duration of MIS 4. Growth recommences during MIS 3, associated with greater moisture availability, enhanced vegetation and augmented biogeochemical cycling. This speleothem record provides a unique context of terrestrial environmental change and depicts hydrological conditions which fluctuate markedly over the 70‐ka period covering the time of megafauna extinction and human arrival on the continent.

Biodiversity only makes sense in the light of evolution - R Geeta; Lúcia G Lohmann; Susana Magallón; Daniel P Faith; Andrew Hendry; Keith Crandall; Luc de Meester; Cam Webb; Anne-Hélène Prieur-Richard; Makiko Mimura; Elena Conti; Joel Cracraft; et al. (Journal of Biosciences, 2014)

Erratum to: Methods to account for tree-scale variability in soil and plant-related parameters in oil palm plantations - P. N. Nelson; M. J. Webb; M. Banabas; S. Nake; I. Goodrick; J. Gordon; D. O’Grady; B. Dubos (Plant and Soil, 2014)

Confirmation of ovarian homogeneity in post-vitellogenic cultured white sturgeon, Acipenser transmontanus - Mariah J. Talbott; Sarah A. Servid; Anna G. Cavinato; Joel P. Van Eenennaam; Serge I. Doroshov; Peter Struffenegger; Molly A.H. Webb (Fish Physiology and Biochemistry, 2014)

Methods to account for tree-scale variability in soil- and plant-related parameters in oil palm plantations - P. N. Nelson; M. J. Webb; M. Banabas; S. Nake; I. Goodrick; J. Gordon; D. O’Grady; B. Dubos (Plant and Soil, 2014)

Coupling between subtropical cloud feedback and the local hydrological cycle in a climate model - Mark. J. Webb; Adrian P. Lock (Climate Dynamics, 2013)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Alteromonas australica sp. nov., isolated from the Tasman Sea - Elena P. Ivanova; Hooi Jun Ng; Hayden K. Webb; Valeriya V. Kurilenko; Natalia V. Zhukova; Valery V. Mikhailov; Olga N. Ponamoreva; Russell J. Crawford (Antonie van Leeuwenhoek, 2013)

Filtration of sea louse, L epeophtheirus salmonis , copepodids by the blue mussel, M ytilus edulis , and the A tlantic sea scallop, P lacopecten magellanicus , under different flow, light and copepodid‐density regimes - A Bartsch; S M C Robinson; M Liutkus; K P Ang; J Webb; C M Pearce (Journal of Fish Diseases, 2013)
Population management of L epeophtheirus salmonis in C anada currently relies on chemotherapeutants to remove attached stages of the ectoparasite. However, some populations of L . salmonis are developing resistance to chemotherapeutants making alternate management measures necessary. This article explores the ability of filter‐feeding shellfish [ i.e . blue mussels ( Mytilus edulis ) and A tlantic sea scallops ( P lacopecten magellanicus )] to consume the copepodid stages of L . salmonis in the laboratory under static and flowing water conditions, with variable copepodid densities, and with the aid of a light attractant. M ytilus edulis consumed copepodids under both static and flowing water conditions, and the proportion of individuals ingested was similar at low and high copepodid densities, suggesting that M . edulis was not saturated at the concentrations tested. Also, M . edulis consumed more copepodids when a light attractant was present, suggesting that lights may be useful to concentrate widely dispersed copepodids around cultured shellfish in the field. Finally, P . magellanicus consumed the same number of copepodids as an equivalent total wet weight of M . edulis . During each of the four separate experiments, shellfish consumed between 18 and 38% of the copepodids presented per hour, suggesting that both species are well suited for low level removal of copepodids over time.

Updating the taxonomic toolbox: classification of Alteromonas spp. using multilocus phylogenetic analysis and MALDI-TOF mass spectrometry - Hooi Jun Ng; Hayden K. Webb; Russell J. Crawford; François Malherbe; Henry Butt; Rachel Knight; Valery V. Mikhailov; Elena P. Ivanova (Antonie van Leeuwenhoek, 2013)

Climate change scenarios to facilitate stakeholder engagement in agricultural adaptation - N. P. Webb; C. J. Stokes (Mitigation and Adaptation Strategies for Global Change, 2012)

A new large scale soil DNA extraction procedure and real-time PCR assay for the detection of Sclerotium cepivorum in soil - James W. Woodhall; Kathryn M. Webb; Patricia M. Giltrap; Ian P. Adams; Jeff C. Peters; Giles E. Budge; Neil Boonham (European Journal of Plant Pathology, 2012)

Intake of omega-3 and omega-6 fatty acids and risk of ovarian cancer - T. I. Ibiebele; C. M. Nagle; C. J. Bain; P. M. Webb (Cancer Causes & Control, 2012)

The significance of carbon‐enriched dust for global carbon accounting - Nicholas P. Webb; Adrian Chappell; Craig L. Strong; Samuel K. Marx; Grant H. McTainsh (Global Change Biology, 2012)
Soil carbon stores amount to 54% of the terrestrial carbon pool and twice the atmospheric carbon pool, but soil organic carbon ( SOC ) can be transient. There is an ongoing debate about whether soils are a net source or sink of carbon, and understanding the role of aeolian processes in SOC erosion, transport and deposition is rudimentary. The impacts of SOC erosion by wind on the global carbon budget, and its importance for carbon accounting remain largely unknown. Current understanding of SOC losses to wind erosion is based on the assumption that the SOC content of eroded material is the same as that of the parent soils. However, measured enrichment factors for the SOC content of A ustralian dusts relative to parent soils show that the SOC content of dusts can be up to seven times (by weight) larger than that of source‐area soils, with enrichment factors ranging from 1.67 to 7.09. Assuming dust emissions from the continent of ~110 Mt yr −1 , SOC dust emissions would be 0.13–4.65 Mt SOC yr −1 without enrichment but 0.94–7.77 Mt SOC yr −1 with enrichment; which represents an uncertainty of around 60%. Representing SOC enrichment within dust emission models will reduce uncertainty in estimates of the impact of wind erosion on SOC flux and provide an approach for the inclusion of wind erosion processes in carbon accounting systems.

Consensus Paper: Pathological Role of the Cerebellum in Autism - S. Hossein Fatemi; Kimberly A. Aldinger; Paul Ashwood; Margaret L. Bauman; Charles D. Blaha; Gene J. Blatt; Abha Chauhan; Ved Chauhan; Stephen R. Dager; Price E. Dickson; Annette M. Estes; Dan Goldowitz; et al. (The Cerebellum, 2012)

Characterizing abundance–occupancy relationships: there is no artefact - Thomas J. Webb; Robert P. Freckleton; Kevin J. Gaston (Global Ecology and Biogeography, 2012)
Positive abundance–occupancy relationships (AORs) are among the most general macroecological patterns: locally common species are regionally widespread, locally rare species are regionally restricted. In a recent contribution, Wilson ( Global Ecology and Biogeography , 2011, 20 , 193–202) made three claims: (1) that AORs are critically dependent on the method used to calculate average abundance; (2) averaging abundance over occupied sites tends to lead to a very high incidence of negative relationships; (3) this represents a statistical artefact that should be considered in studies of AORs. Here we show that this outcome arises in Wilson's simulations purely due to an arbitrary choice of occupancy models and parameter ranges. The resulting negative relationships are not statistical artefacts, but are easily interpreted in terms of spatial aggregation in abundant species. The fact that empirical evidence fails to support a high prevalence of negative AORs suggests, however, that such parameter combinations arise only rarely in nature. We conclude that simulations that are based on untested assumptions, and that produce patterns unsupported by empirical evidence, have limited use in characterizing AORs, and add little to understanding of the processes driving important relationships between local population size and regional occupancy.

Interacting effects of vegetation, soils and management on the sensitivity of Australian savanna rangelands to climate change - Nicholas P. Webb; Chris J. Stokes; Joe C. Scanlan (Climatic Change, 2012)

The toxic effects of three dinoflagellate species from the genus Karenia on invertebrate larvae and finfish - F Shi; P McNabb; L Rhodes; P Holland; S Webb; J Adamson; A Immers; R Gooneratne; J Holland (New Zealand Journal of Marine and Freshwater Research, 2012)
Three species of Kareniaceae, Karenia brevis , Karenia brevisulcata and Karenia mikimotoi were assessed for toxicity to juvenile Chinook salmon ( Oncorhynchus tshawytscha ), snapper ( Pagrus auratus ) and six species of marine invertebrate larvae (Greenshell TM mussel, pacific oyster, paua [New Zealand abalone], sea slug, sea urchin and brine shrimp). Karenia brevis was ichthyotoxic to juvenile salmon with a LT 50 of 0.75 h at 0.18 × 10 6 cells L –1 but juvenile snapper were less sensitive (LT 50 of 4.5 h at 5.9 × 10 6 cells L –1 ). Karenia brevisulcata also showed differential toxicity to juvenile salmon and snapper with LT 50 of 0.48 h at 11 × 10 6 cells L –1 and 7.5 h at 16 × 10 6 cells L –1 respectively. However, no acute symptoms were observed in the fish following 48 h exposure to K. mikimotoi at 3.4 × 10 6 cells L –1 . Karenia brevis at the highest level tested (8.7 × 10 6 cells L –1 ) did not cause observable symptoms in any of the invertebrate larvae over 24 h. Karenia mikimotoi only affected paua larvae (LT 50 10 h at 12 × 10 6 cells L –1 ). Karenia brevisulcata was highly toxic to mussel, sea urchin and paua larvae (LT 50 1–6.1 h at 7.5–9.6 × 10 6 cells L –1 ), toxic to sea slug and oyster larvae (LT 50 6 h at 80 × 10 6 cells L –1 and 9.2 h at 34 × 10 6 cells L –1 respectively) but did not affect brine shrimp. Analysis of test cultures by liquid chromatography‐mass spectrometry confirmed that K. brevis produced brevetoxins (52 pg cell –1 ; mainly brevetoxin‐2). Karenia brevisulcata produced brevisulcatic acids (BSXs) and the more toxic Karenia brevisulcata toxins (KBTs). Karenia mikimotoi did not produce brevetoxin, BSXs or KBTs. The present study confirms the broad threats that blooms of K. brevisulcata pose to marine ecosystems and aquaculture, and the hazards of K. brevis to finfish and K. mikimotoi to abalone respectively.

Automated multidimensional single molecule fluorescence microscopy feature detection and tracking - Daniel J. Rolfe; Charles I. McLachlan; Michael Hirsch; Sarah R. Needham; Christopher J. Tynan; Stephen E. D. Webb; Marisa L. Martin-Fernandez; Michael P. Hobson (European Biophysics Journal, 2011)

Viability of cattle sperm under different storage conditions in Cameroon - P. H. Bayemi; I. Leinyuy; V. M. Nsongka; E. C. Webb; A. L. Ebangi (Tropical Animal Health and Production, 2010)

A molecular assessment of the iron stress response in the two phylogenetic clades of Trichodesmium - P. Dreux Chappell; Eric A. Webb (Environmental Microbiology, 2010)
Summary Trichodesmium spp. play key roles in global carbon and nitrogen budgets and thus defining what controls their productivity is important for understanding climate change. While iron availability has been shown to be an important chemical factor for controlling both growth and nitrogen fixation rates in Trichodesmium , all culture experiments to date have focused solely on representatives from one clade of Trichodesmium . Genomic sequence analysis determined that the Trichodesmium erythraeum (IMS101) genome contains many of the archetypical genes involved in the prokaryotic iron stress response. Focusing on three of these genes, isiB , idiA and feoB , we found that all three showed an iron stress response in axenic T. erythraeum (IMS101), and their sequences were well conserved across four species in our Trichodesmium culture collection [consisting of two T. erythraeum strains (IMS101 and GBRTRLI101), two Trichodesmium tenue strains (Z‐1 and H9‐4), Trichodesmium thiebautii and Trichodesmium spiralis ]. With clade‐specific quantitative PCR (qPCR) primers for one of these genes, isiB , we found that high isiB expression at low Fe levels corresponded to specific reductions in N 2 fixation rates in both major phylogenetic clades of Trichodesmium (the T. erythraeum clade and T. tenue clade). With regard to the two clades, the most significant difference determined was temperature optima, while more subtle differences in growth, N 2 fixation rate and gene expression responses to Fe stress were also observed. However the apparent conservation of the Fe stress response in the Trichodesmium genus suggests that it is an important adaptation for their niche in the oligotrophic ocean.

Impact of management interventions on smallholder dairy farms of the western highlands of cameroon - P. H. Bayemi; E. C. Webb; A. Ndambi; F. Ntam; V. Chinda (Tropical Animal Health and Production, 2009)

An integrated method for improving the dairy production sector in developing countries: the case of Cameroon - P. H. Bayemi; E. C. Webb (Tropical Animal Health and Production, 2009)

Prevalence of Brucella abortus antibodies in serum of Holstein cattle in Cameroon - P. H. Bayemi; E. C. Webb; M. V. Nsongka; H. Unger; H. Njakoi (Tropical Animal Health and Production, 2009)

Effects of 12 hour calf withdrawal on conception rate and calf performance of Bos indicus cattle under extensive conditions - R. J. A. Escrivão; E. C. Webb; A. P. J. T. Garcês (Tropical Animal Health and Production, 2009)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

EhaA is a novel autotransporter protein of enterohemorrhagic Escherichia coli O157:H7 that contributes to adhesion and biofilm formation - Timothy J. Wells; Orla Sherlock; Lucy Rivas; Arvind Mahajan; Scott A. Beatson; Mia Torpdahl; Richard I. Webb; Luke P. Allsopp; Kari S. Gobius; David L. Gally; Mark A. Schembri (Environmental Microbiology, 2008)
Summary Autotransporter (AT) proteins have been identified in many Gram‐negative pathogens and are unique in that their primary sequence is sufficient to direct their transport across the bacterial membrane system. Where characterized they are uniformly associated with virulence. Using conserved AT motifs as a search tool, four putative AT proteins were identified in the Enterohemorrhagic Escherichia coli O157:H7 EDL933 genome. The genes encoding these proteins (z0402/ ehaA , z0469/ ehaB , z3487/ ehaC and z3948/ ehaD ) were PCR amplified, cloned and expressed in an E. coli K‐12 MG1655 flu background. Preliminary characterization revealed that ehaA , ehaB and ehaD encode proteins associated with increased biofilm formation. One of these genes ( ehaA ) resides on a genomic island in E. coli O157:H7 strains EDL933 and Sakai. Over‐expression of EhaA in E. coli K‐12 demonstrated it is located at the cell surface and resulted in the formation of large cell aggregates, promoted significant biofilm formation and mediated adhesion to primary epithelial cells of the bovine terminal rectum. The expression of ehaA was demonstrated in E. coli EDL933 by RT‐PCR. An EhaA‐specific antibody revealed the EhaA protein was expressed in 24/50 generic Shiga toxin‐producing E. coli (STEC) strains of various serotypes including O157:H7. However, the deletion of ehaA from E. coli EDL933 and a STEC strain from serotype O111:H – did not affect biofilm growth. Our results suggest that EhaA may contribute to adhesion, colonization and biofilm formation by E. coli O157:H7 and possibly other STEC serotypes.

Forest Value Orientations in Australia: An Application of Computer Content Analysis - Trevor J. Webb; David N. Bengston; David P. Fan (Environmental Management, 2008)

Economic opportunity survey of small scale dairy farms of the north west province of Cameroon - P. H. Bayemi; E. C. Webb; Y. Manjeli; P. Naoussi (Tropical Animal Health and Production, 2007)

Decadal- to interannual-scale source water variations in the Caribbean Sea recorded by Puerto Rican coral radiocarbon - K. Halimeda Kilbourne; Terrence M. Quinn; Thomas P. Guilderson; Robert S. Webb; Frederick W. Taylor (Climate Dynamics, 2007)

Validation of a human progesterone enzyme immunoassay (EIA) kit for use on serum of cattle in Cameroon - P. H. Bayemi; V. M. Nsongka; B. M. A. O. Perera; D. Cavestany; E. C. Webb (Tropical Animal Health and Production, 2007)

A model of antennal wall-following and escape in the cockroach - T. P. Chapman; B. Webb (Journal of Comparative Physiology A, 2006)

The Snellen human calorimeter revisited, re-engineered and upgraded: design and performance characteristics - Francis D. Reardon; Kalle E. Leppik; René Wegmann; Paul Webb; Michel B. Ducharme; Glen P. Kenny (Medical & Biological Engineering & Computing, 2006)

Insulation disks on the skin to estimate muscle temperature - Dragan Brajkovic; Michel B. Ducharme; Paul Webb; Frank D. Reardon; Glen P. Kenny (European Journal of Applied Physiology, 2006)

Geochemistry of Early–Middle Palaeozoic basalts in the Hodgkinson Province: a key to tectono-magmatic evolution of the Tasman Fold Belt System in northeastern Queensland, Australia - I. M. A. Vos; F. P. Bierlein; J. Webb (International Journal of Earth Sciences, 2006)

Transient expression and insertional mutagenesis of Puccinia triticina using biolistics - Craig A. Webb; Les J. Szabo; Guus Bakkeren; Clarke Garry; Richard C. Staples; Merle Eversmeyer; John P. Fellers (Functional & Integrative Genomics, 2006)

Quantifying Abrasion of Stable Substrata in Streams: A New Disturbance Index for Epilithic Biota - J. Angus Webb; Barbara J. Downes; P. S. Lake; Alena Glaister (Hydrobiologia, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Antibody-based therapeutics: Focus on prostate cancer - Jeffrey S. Ross; Karen E. Gray; Iain J. Webb; Gary S. Gray; Mark Rolfe; David P. Schenkein; David M. Nanus; Mathew I. Millowsky; Neil H. Bander (Cancer and Metastasis Reviews, 2005)

Forest Health, Collective Behaviors, and Management - Nitaya Kijtewachakul; Ganesh P. Shivakoti; Edward L. Webb (Environmental Management, 2004)

Forest Cover Change, Physiography, Local Economy, and Institutions in a Mountain Watershed in Nepal - Ambika P. Gautam; Ganesh P. Shivakoti; Edward L. Webb (Environmental Management, 2004)

A floristic analysis of the lowland dipterocarp forests of Borneo - J. W. F. Slik; A. D. Poulsen; P. S. Ashton; C. H. Cannon; K. A. O. Eichhorn; K. Kartawinata; I. Lanniari; H. Nagamasu; M. Nakagawa; M. G. L. Van Nieuwstadt; J. Payne; Purwaningsih; et al. (Journal of Biogeography, 2003)
Aim To (1) identify floristic regions in the lowland (below 500 m a.s.l.) tropical dipterocarp rain forest of Borneo based on tree genera, (2) determine the characteristic taxa of these regions, (3) study tree diversity patterns within Borneo, and (4) relate the floristic and diversity patterns to abiotic factors such as mean annual rainfall and geographical distance between plots. Location Lowland tropical dipterocarp rain forest of Borneo. Methods We used tree (diameter at breast height ≥ 9.8 cm) inventory data from 28 lowland dipterocarp rain forest locations throughout Borneo. From each location six samples of 640 individuals were drawn randomly. With these data we calculated a Sørensen and Steinhaus similarity matrix for the locations. These matrices were then used in an UPGMA clustering algorithm to determine the floristic relations between the locations (dendrogram). Principal coordinate analysis was used to ordinate the locations. Characteristic taxa for the identified floristic clusters were determined with the use of the INDVAL method of Dufrene & Legendre (1997) . Finally, Mantel analysis was applied to determine the influence of mean annual rainfall and geographical distance between plots on floristic composition. Results A total of 77 families and 363 genera were included in the analysis. On average a random sample of 640 trees from a lowland dipterocarp forest in Borneo contains 41.6 ± 3.8 families and 103.0 ± 12.7 genera. Diversity varied strongly on local scales. On a regional scale, diversity was found to be highest in south‐east Borneo and central Sarawak. The most common families were Dipterocarpaceae (21.9% of trees) and Euphorbiaceae (12.2% of trees). The most common genera were Shorea (12.3% of trees) and Syzygium (5.0% of trees). The 28 locations were clustered in geographically distinct floristic regions. This was related to the fact that floristic similarity depended strongly on the geographical distance between plots and similarity in mean annual rainfall. Conclusions We identified five main floristic regions within the lowland dipterocarp rain forests of Borneo, each of which had its own set of characteristic genera. Mean annual rainfall is an important factor in explaining differences in floristic composition between locations. The influence of geographical distance on floristic similarity between locations is probably related to the fact that abiotic factors change with distance between plots. Borneo's central mountain range generally forms an effective dispersal barrier for the lowland tree flora. Diversity patterns in Borneo are influenced by the mid‐domain effect, habitat size and the influence of past climatic changes (ice ages during the Pleistocene).

Synergistic interactions between chemical alarm cues and the presence of conspecific and heterospecific fish shoals - Brian D. Wisenden; Mike S. Pollock; Robyn J. Tremaine; Jeff M. Webb; Monique E. Wismer; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2003)

A high-Arctic population of Pyla fusca (Lepidoptera, Pyralidae) on Svalbard? - S. J. Coulson; I. D. Hodkinson; N. R. Webb; P. Convey (Polar Biology, 2003)

A new biomineral identified in the cores of teeth from the chiton Plaxiphora albida - Alasdair P. Lee; Lesley R. Brooker; David J. Macey; John Webb; Wilhelm van Bronswijk (JBIC Journal of Biological Inorganic Chemistry, 2003)

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

Evaluating the coastal environment for marine birds - S. Wanless; P. J. Bacon; M. P. Harris; A. D. Webb (Journal of Coastal Conservation, 2002)

The effects of copper on the microbial community of a coral reef sponge - Nicole S. Webster; Richard I. Webb; Michael J. Ridd; Russell T. Hill; Andrew P. Negri (Environmental Microbiology, 2001)
Marine sponges often harbour communities of symbiotic microorganisms that fulfil necessary functions for the well‐being of their hosts. Microbial communities associated with the sponge Rhopaloeides odorabile were used as bioindicators for sublethal cupric ion (Cu 2+ ) stress. A combined strategy incorporating molecular, cultivation and electron microscopy techniques was adopted to monitor changes in microbial diversity. The total density of sponge‐associated bacteria and counts of the predominant cultivated symbiont (α‐proteobacterium strain NW001) were significantly reduced in response to Cu 2+ concentrations of 1.7 µg l −1 and above after 14 days of exposure. The number of operational taxonomic units (OTUs) detected by restriction fragment length polymorphism (RFLP) decreased by 64% in sponges exposed to 223 µg l −1 Cu 2+ for 48 h and by 46% in sponges exposed to 19.4 µg l −1 Cu 2+ for 14 days. Electron microscopy was used to identify 17 predominant bacterial morphotypes, composing 47% of the total observed cells in control sponges. A reduction in the proportion of these morphotypes to 25% of observed cells was evident in sponges exposed to a Cu 2+ concentration of 19.4 µg l −1 . Although the abundance of most morphotypes decreased under Cu 2+ stress, three morphotypes were not reduced in numbers and a single morphotype actually increased in abundance. Bacterial numbers, as detected using fluorescence in situ hybridization (FISH), decreased significantly after 48 h exposure to 19.4 µg l −1 Cu 2+ . Archaea, which are normally prolific in R. odorabile , were not detected after exposure to a Cu 2+ concentration of 19.4 µg l −1 for 14 days, indicating that many of the microorganisms associated with R. odorabile are sensitive to free copper. Sponges exposed to a Cu 2+ concentration of 223 µg l −1 became highly necrosed after 48 h and accumulated 142 ± 18 mg kg −1 copper, whereas sponges exposed to 19.4 µg l −1 Cu 2+ accumulated 306 ± 15 mg kg −1 copper after 14 days without apoptosis or mortality. Not only do sponges have potential for monitoring elevated concentrations of heavy metals but also examining changes in their microbial symbionts is a novel and sensitive bioindicator for the assessment of pollution on important microbial communities.

Regulation of neutrophil apoptosis: A role for protein kinase C and phosphatidylinositol-3-kinase - P. R. Webb; K.-Q. Wang; D. Scheel-Toellner; J. Pongracz; M. Salmon; J. M. Lord (Apoptosis, 2000)

Comparison of physical characteristics between created and natural estuarine marshes in Galveston Bay, Texas - Tim P. Delaney; James W. Webb; Thomas J. Minello (Wetlands Ecology and Management, 2000)

Last glacial maximum biomes reconstructed from pollen and plant macrofossil data from northern Eurasia - P. E. Tarasov; V. S. Volkova; T. Webb; J. Guiot; A. A. Andreev; L. G. Bezusko; T. V. Bezusko; G. V. Bykova; N. I. Dorofeyuk; E. V. Kvavadze; I. M. Osipova; N. K. Panova; et al. (Journal of Biogeography, 2000)
Pollen and plant macrofossil data from northern Eurasia were used to reconstruct the vegetation of the last glacial maximum (LGM: 18,000 ± 2000 14 C yr bp ) using an objective quantitative method for interpreting pollen data in terms of the biomes they represent ( Prentice et al. , 1996 ). The results confirm previous qualitative vegetation reconstructions at the LGM but provide a more comprehensive analysis of the data. Tundra dominated a large area of northern Eurasia (north of 57°N) to the west, south and east of the Scandinavian ice sheet at the LGM. Steppe‐like vegetation was reconstructed in the latitudinal band from western Ukraine, where temperate deciduous forests grow today, to western Siberia, where taiga and cold deciduous forests grow today. The reconstruction shows that steppe graded into tundra in Siberia, which is not the case today. Taiga grew on the northern coast of the Sea of Azov, about 1500 km south of its present limit in European Russia. In contrast, taiga was reconstructed only slightly south of its southern limit today in south‐western Siberia. Broadleaved trees were confined to small refuges, e.g. on the eastern coast of the Black Sea, where cool mixed forest was reconstructed from the LGM data. Cool conifer forests in western Georgia were reconstructed as growing more than 1000 m lower than they grow today. The few scattered sites with LGM data from the Tien‐Shan Mountains and from northern Mongolia yielded biome reconstructions of steppe and taiga, which are the biomes growing there today.

A modified Bläzka–type respirometer for the study of swimming metabolism in fishes having deep, laterally compressed bodies or unusual locomotor modes - J. R. Hove; M. S Gordon; P. W. Webb; D. Weihs (Journal of Fish Biology, 2000)
A low volume (8·4 l), rectangular (cross–section) respirometer modified from a Bläzka–type coaxial circuit, which provides rectilinear flow at speeds up to 0·36 m s –1 , is described.

Renal effects of cyclooxygenase inhibitors in volume-depleted dogs - David P. Brooks; Jerry Adams; P. Dennis DePalma; Edward F. Webb; Robert H. Palmer; Don E. Griswold (Inflammopharmacology, 2000)

Allele-specific hybridization markers for soybean - V. H. Coryell; H. Jessen; J. M. Schupp; D. Webb; P. Keim (Theoretical and Applied Genetics, 1999)

In situ Raman spectroscopic studies of the teeth of the chiton Acanthopleura hirtosa - Alasdair P. Lee; John Webb; D. J. Macey; Wilhelm van Bronswijk; Angela R. Savarese; G. Charmaine de Witt (JBIC Journal of Biological Inorganic Chemistry, 1998)

Present‐day and mid‐Holocene biomes reconstructed from pollen and plant macrofossil data from the former Soviet Union and Mongolia - Pavel E. Tarasov; Thompson Webb III; Andrei A. Andreev; Natalya B. Afanas’eva; Natalya A. Berezina; Ludmila G. Bezusko; Tatyana A. Blyakharchuk; Natalia S. Bolikhovskaya; Rachid Cheddadi; Margarita M. Chernavskaya; Galina M. Chernova; Nadezhda I. Dorofeyuk; et al. (Journal of Biogeography, 1998)
Fossil pollen data supplemented by tree macrofossil records were used to reconstruct the vegetation of the Former Soviet Union and Mongolia at 6000 years. Pollen spectra were assigned to biomes using the plant‐functional‐type method developed by Prentice et al . (1996). Surface pollen data and a modern vegetation map provided a test of the method. This is the first time such a broad‐scale vegetation reconstruction for the greater part of northern Eurasia has been attempted with objective techniques. The new results confirm previous regional palaeoenvironmental studies of the mid‐Holocene while providing a comprehensive synopsis and firmer conclusions. West of the Ural Mountains temperate deciduous forest extended both northward and southward from its modern range. The northern limits of cool mixed and cool conifer forests were also further north than present. Taiga was reduced in European Russia, but was extended into Yakutia where now there is cold deciduous forest. The northern limit of taiga was extended (as shown by increased Picea pollen percentages, and by tree macrofossil records north of the present‐day forest limit) but tundra was still present in north‐eastern Siberia. The boundary between forest and steppe in the continental interior did not shift substantially, and dry conditions similar to present existed in western Mongolia and north of the Aral Sea.

Rpg1, a soybean gene effective against races of bacterial blight, maps to a cluster of previously identified disease resistance genes - T. Ashfield; J. R. Danzer; D. Held; K. Clayton; P. Keim; M. A. Saghai Maroof; D. M. Webb; R. W. Innes (Theoretical and Applied Genetics, 1998)

Physiological and morphological variation in Metrosideros polymorpha , a dominant Hawaiian tree species, along an altitudinal gradient: the role of phenotypic plasticity - S. Cordell; G. Goldstein; D. Mueller-Dombois; D. Webb; P. M. Vitousek (Oecologia, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Failure of systemic insecticide-nematicides to affect total glycoalkaloid content of harvested potato tubers in northern Florida - D. P. Weingartner; J. R. Shumaker; R. E. Webb (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Parana, a new tacaribe complex virus from Paraguay - P. A. Webb; K. M. Johnson; J. B. Hibbs; M. L. Kuns (Archives of Virology, 1970)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)